Diversity of Insect Species on Bird's Eye Chili Pepper (Capsicum frutescens L.) in Tudua Village, Morowali Regency - Nurul Amna Moh Said; Fatmah Dhafir; Syech Zainal; Manap Trianto; Sutrisnawati Sutrisnawati; Masrianih Masrianih (Biology, Medicine, & Natural Product Chemistry, 2026)
Insects are the most diverse group of living organisms, accounting for nearly 80% of all known animal species. They belong to the phylum Arthropoda and exhibit a wide range of morphological characteristics. Insects can be found in almost all habitats, ranging from lush tropical rainforests to harsh deserts, as well as aquatic environments such as rivers and lakes. This study aimed to identify and describe insect species associated with bird's eye chili pepper (Capsicum frutescens L.) in Tudua Village. The research was conducted in October 2025. The study sites were selected using purposive sampling, with three observation plots measuring 10 × 10 m each. Insect samples were collected using a combination of sweeping nets, pitfall traps, light traps, and yellow traps. The collected specimens were identified based on their morphological characteristics up to the order, family, genus, or species level and were analyzed descriptively to determine their ecological roles within the agroecosystem. The results revealed a total of 29 insect species belonging to eight orders: Araneae, Coleoptera, Hemiptera, Orthoptera, Odonata, Lepidoptera, Hymenoptera, and Blattodea. The identified insects exhibited diverse ecological roles, including pests, herbivores, predators, pollinators, and decomposers. Members of the order Hemiptera and some species of Coleoptera were the most commonly encountered pest groups. Meanwhile, Araneae, Hymenoptera, and Odonata functioned as natural predators, Lepidoptera acted as pollinators, and Blattodea served as decomposers. The presence and distribution of insects were influenced by environmental factors such as temperature, humidity, light intensity, and soil pH.